Financial intermediation chains in an OTC market - Ji Shen; Bin Wei; Hongjun Yan (Federal Reserve Bank of Atlanta, 2018)
This paper analyzes financial intermediation chains in a search model with an endogenous intermediary sector. We show that the chain length and price dispersion among interdealer trades are decreasing in search cost, search speed, and market size but increasing in investors' trading needs. Using data from the U.S. corporate bond market, we find evidence broadly consistent with these predictions. Moreover, as search speed approaches infinity, the search equilibrium does not always converge to the centralized-market equilibrium: prices and allocation converge, but the trading volume might not. Finally, we analyze the multiplicity and stability of the equilibrium.
Keywords: G10; 330; search; chain; financial intermediation; multiplicity; stability